Analysis Socioeconomic Influence on the Utilization of Health Service in the Inpatient Room of Faisal Islamic Hospital Makassar - Arifin, Muhammad Alwy; Amriani. AS, Amaliah; Abadi, Muh. Yusri; Mallongi, Anwar; Marzuk, Dian Saputra (International Journal of Criminology and Sociology, 2021)
Hospitals in carrying out their role cannot be separated from problems, both from within and from outside that can interfere with the mechanism of work of the hospital in providing health services for the community. Faisal Islamic Hospital Makassar is one of the private hospitals in the city of Makassar which in the last 3 years has decreased the value of BOR. The purpose of this study was to find out the socio-economic influence on the utilization of health services in the inpatient room of Faisal Islamic Hospital Makassar. This research is a cross-sectional study. A total of 99 people were sampled in the inpatient room of Faisal Islamic Hospital Makassar by taking a sample using the purposive sampling method. Data is collected by conducting interviews with respondents. Data processing is done by frequency distribution analysis and univariate and multivariate analysis with the Binary Regression approach namely logit and probit analysis. Based on the results of the study, it was obtained that socioeconomic variables that have an influence on the utilization of health services in the Faisal Islamic Hospital Makassar is the ownership of health insurance with the results of p-value< 0.1 is logit 0.299 and probit of 0.000. For the government to evaluate the ownership of health insurance, because there are still respondents who do not have health insurance where this is not in accordance with the objectives of the National Health Insurance program.